AGEFLEX - VERSATILITY IN SCHEDULING CONTROL SPACES (CIPEEX, 2024)
This paper presents the development of AgeFlex, a scheduling system forinstitutional environments. Its objective is to enhance space management ininstitutions, particularly in the educational sector. The introduction emphasizes theimportance of technology in everyday life and its role as a tool to assist organizationsin adapting to changes and remaining competitive. Within the academic context,efficient space management is essential to ensure proper organization and utilization.However, many institutions face challenges due to the complexity of scheduling andthe increasing demand for different types of spaces. Ageflex emerges as a solution tooptimize the scheduling process, making it more efficient and tailored to users’needs. The system also aims to be safe and efficient, with a friendly interface thatintegrates perfectly with institutional routines. The solution uses technologies such asMySQL, PHP, and Laravel, with a focus on usability and integration, along with theimplementation of the Entity Attribute Value (EAV) paradigm to enhance dataflexibility. Ageflex aims to pave the way for more efficient and dynamic administration,maximizing resource utilization and delivering a satisfactory managementexperience.
Keywords: Scheduling system. Institutional spaces. Technology. Management. Entity Attribute Value (EAV). Flexibility